2004
DOI: 10.1159/000080585
|View full text |Cite
|
Sign up to set email alerts
|

Acid Resistance of Enamel Subsurface Lesions Remineralized by a Sugar-Free Chewing Gum Containing Casein Phosphopeptide-Amorphous Calcium Phosphate

Abstract: The aim of this clinical study was to investigate the acid resistance of enamel lesions remineralized in situ by a sugar-free chewing gum containing casein phosphopeptide-amorphous calcium phosphate nanocomplexes (CPP-ACP: Recaldent™). The study utilized a double-blind, randomized, crossover design with two treatments: (i) sugar-free gum containing 18.8 mg of CPP-ACP, and (ii) sugar-free gum not containing CPP-ACP as control. Subjects wore removable palatal appliances with insets of human enamel containing dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
174
0
27

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(225 citation statements)
references
References 26 publications
18
174
0
27
Order By: Relevance
“…CPP-ACP has been shown to adhere to the bacterial wall of microorganisms and tooth surfaces [37]. When an intraoral acid attack occurs, the calcium and phosphate ions are released to produce a supersaturated concentration of ions in the saliva, which then precipitates a calcium-phosphate compound onto the exposed tooth surface [38]. A few studies showed that daily applications of the remineralizing cream could reverse the severity and visual appearance of postorthodontic WSLs more effectively than fluoride toothpaste.…”
Section: Use Of Casein Phosphopeptides Amorphous Calcium Phosphatementioning
confidence: 99%
“…CPP-ACP has been shown to adhere to the bacterial wall of microorganisms and tooth surfaces [37]. When an intraoral acid attack occurs, the calcium and phosphate ions are released to produce a supersaturated concentration of ions in the saliva, which then precipitates a calcium-phosphate compound onto the exposed tooth surface [38]. A few studies showed that daily applications of the remineralizing cream could reverse the severity and visual appearance of postorthodontic WSLs more effectively than fluoride toothpaste.…”
Section: Use Of Casein Phosphopeptides Amorphous Calcium Phosphatementioning
confidence: 99%
“…Orthodontic appliances as such are not a cause of demineralization or caries, but creation of new retentive sites could result in oral hygiene problems when Orthodontic appliances are worn [10].…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan çalışmalarda sakız içerisine eklenen CPP-ACP nin remineralizasyonu zenginleştirdiği gözlenmiştir. Ancak bu durumun CPP-ACP'den mi kaynaklandığı yada sakızların kullanımıyla tükürük uyarılmasından dolayı mı kaynaklandığı soru işaretidir 70,71 . Şekersiz sakız kullanımı genellikle sabit ortodontik apareylerin kullanılmasından sonra tavsiye edilmektedir.…”
Section: Kazein Fosfopeptid Amorf Kalsiyum Fosfat (Cpp-acp)unclassified